Fungsi Ujaran Pada Percakapan Siswa di Kelas Bahasa Inggris: Studi Semantik - Ayu Isa Putri, Leila; Saibani Wiyanto, Muhammad (Universitas Nusantara PGRI Kediri, 2024)
The article aims to investigate speech function on student conversation in English classroom related with Halliday (1994) approach. This articleis a qualitative research design. Content or document analysis is used in this study. The data source is students’ conversations in class XI in English classroom at MAN 5 Jombang. The data in this article are sentences and clauses which represent the type and meaning of speech function on students conversation in English classroom. The instrument was smartphonewith an integrated camera to record video and audio. The recorded data were converted through transcription. The results showed that the students used three types of speech functions: statement, command, and question, but the offer type was not used by students. The statement type was often used by students in class. Meanwhile, there were three meanings of speech functions used by students, namely, giving information (statement), demanding goods-&-services (command), and demanding information (question). It could be seen that students applied elements of speech function. It is implied that the development of interactive activities and continuous evaluation are important to improve students' practical communication skills.Lecturers are encouraged to conduct more dynamic interactions in class with activities that stimulate the use of commands and questions.